The Role of Parents in the Moral Development of Early Childhood - Fatiyah Qailani; Khoerunnisa Nurfadilah; Zulfa Syarifah (Beginner: Journal of Teaching and Education Management, 2024)
The moral development of early childhood is something that adults, especially parents, must pay attention to. Parents are the first and main social environment for children's growth and development. Therefore, the author conducted this research with the aim of analyzing the role of parents in early childhood development. This research is qualitative research with a literature study type of research. The data source used is a literature review from various sources related to the moral development of early childhood such as articles, journals or books. The data analysis technique used is by reducing data, analyzing data, and drawing conclusions. The results of this research show that parents have a very important role in children's moral development. Moral development in early childhood is a long series of processes acquired by children through experience, teaching and education about what is wrong and what is right. Therefore, parents must play the role of educators, the role of encouragement, the role of role models, the role of friends, the role of counselors, and the role of communicators. Apart from that, parents also act as facilitators and companions for children in the process of developing their morality. There are factors that influence a child's moral development, such as the child's personal context and the child's social context when socializing in the environment.